PWE-091 Are Qualitative Faecal Calprotectin Assays Useful in Clinical Practice?. (4th June 2013) - Pee, L; Josephs, K; McNair, A
Abstract : Introduction: Distinguishing organic and functional bowel disease is often clinically difficult. Faecal biomarkers have been used to aid the diagnosis of inflammatory bowel disease (IBD) and reduce the need for invasive investigations. Quantitative faecal calprotectin (CAL) at certain thresholds has been shown to have a high sensitivity and specificity for identifying IBD. There is also similar evidence for faecal lactoferrin (LAC). There is less evidence for the use of point of care qualitative assays in clinical practise, however previously it has demonstrated comparable efficacy to the quantitative test. Methods: This is a retrospective study of 528 patients with abdominal symptoms who had faecal CAL measured (Quantum Blue® LFCAL) from June 2011 to June 2012 in Queen Elizabeth Hospital, Woolwich and Queen Mary's Hospital, Sidcup. Faecal LAC (IBD EZ VUE®) was only measured when CAL was positive. The tests were ordered by both hospital physicians and general practitioners (GPs). Definitive outcome for hospital patients was determined by blood tests, endoscopy with histology and further imaging. Outcome was not recorded for patients with a negative test result. Results: 136 patients had positive CAL and therefore also had LAC measured. 392 patients had negative CAL. Outcome was not known for 42/136 patients as these tests were ordered by GPs and they possibly attended other hospitals. Some tests were carried out to assess patients with known IBD (15 tests total – 7 CAL +/LAC -, 8 CAL +, LAC +). 121 patients with positive CAL had the test for primary diagnostic purposes. 60 patients had a positive CAL and a negative LAC, of which47/60 (78%) had normal colonoscopies; 13/60 (22%) had an abnormal result. 34 patients had a positive CAL and a positive LAC, of which 10/34 (29%) had normal colonoscopies; 24/34 (71%) had an abnormal result. Conclusion: In this study, a positive qualitative CAL result was a poor marker of bowel inflammation. The number of false positive results was greatly reduced by using it in conjunction with LAC, 29% in comparison to 78%. Qualitative CAL may be useful at excluding IBD when it is negative and the threshold is low, however, our data shows that a positive test is not specific and cannot be compared to a quantitative CAL test. This may be because of the low threshold of our particular test (30–300 ng/ml) and qualitative LAC testing may improve this. Disclosure of Interest: None Declared.